Aktivitas Sosial Religius Perspektif Pemberdayaan Di Masjid Agung Nurul Iman Kota Padang - Deka Putra; Awis Karni; Irta Sulastri (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
The religious social activity at the Great Nurul Iman mosque in Padang City is not only seen as a place of prayer, but also empowers the people. Mosque is a traditional place to mobilize da'wah, and also a community development center, an information center and developing knowledge education and training and social activities. The objectives of this study are to reveal Tahfizd's activities, the hadith activities of Ar-ba'in and the gold savings activity for orphan education at the Agung Nurul Iman mosque in Padang. The type of this research is descriptive qualitative, which describes how to describe the facts and symptoms that exist in the field. Data collection techniques used were observation, interviews, and documentation. The research results obtained in the study are: (1) Tahfzd coaching activities at the Agung Nurul Iman mosque in Padang City have been going well, with the existence of tahfizd activities and can add and improve the memorization of students. (2). The ar-ba'in hadith program at the Nurul Iman mosque in Padang City can add insight and knowledge of the congregation about the hadiths taught by the Prophet Muhammad such as the procedures for living, prayer, fasting, zakat, and the history of Islam (3). The gold saving activity at the Agung Nurul Iman mosque in Padang City can help with the needs and costs of education for orphans who are registered in the gold savings activity.